Convection heat transfer from a laminar flow over a 2-D backward facing step with asymmetric and orthotropic porous floor segments - Abu-Hijleh, Bassam (1997)
The fluid and energy equations for the incompressible laminar reattaching flow over a 2-D backward facing step with a porous floor segment were solved numerically using the finite element method. The focus of this study was the change in die forced convection heat transfer characteristics of the flow field due to the addition of a porous floor segment. Several porous flow segment configurations with different lengths and depths were studied. The effect of orthotropicity of the porous segments was also studied. The porosity of the segments was varied over a wide range by changing the value of the pressure loss coefficients in either or both of the x and y directions. The changes in the local and overall Nusselt numbers were reported and discussed. Depending on the configuration, the overall Nusselt number increased or decreased relative to the case of a solid floor. For all configurations, the maximum local Nusselt number increased.